Anatomy for art students creating a three-dimensional sculpted model of the human anatomy as visual reference and instructional aid in teaching figure drawing to fine arts students - Mendoza, Naomi Alianne B.
The ability to produce effective learners lies in the capacity to progress in the development of materials and tools sufficient for learning. As technology advances, learners must also be equipped with the proper tools in order to effectively communicate and maximize knowledge in the subject matter.